Effect of anandamide on endometrial adenocarcinoma (Ishikawa) cell numbers: implications for endometrial cancer therapy. (26th February 2015) - Ayakannu, Thangesweran; Taylor, Anthony; Willets, Jonathon; Marczylo, Timothy; Brown, Laurence; Davies, Quentin; Moss, Esther; Konje, Justin
Abstract: Background: We have previously shown that patients with endometrial carcinoma express elevated concentrations of the endocannabinoid, anandamide (AEA), in both their plasma and their endometrial tissue and that the endometrial carcinoma cell line, Ishikawa, contains the receptors to which AEA binds. Several studies have reported that human and rodent cancer cell lines die in response to high AEA concentrations. The incidence of endometrial carcinoma continues to escalate and, although surgical treatment has improved, morbidity and mortality rates have not. A move towards a novel non-surgical therapeutic option is thus required, and the endocannabinoid system provides a good candidate target. We aimed to investigate the effects of AEA on the survival and proliferation of an endometrial carcinoma cell model. Methods: This prospective basic research study was conducted at a UK teaching hospital. Ishikawa cells were cultured in vitro, and a range of AEA concentrations (0–10 000 nM) were added to the cells. The effect of AEA was measured at different timepoints (4, 18, 24, 48, and 72 h). Primary outcome was cell proliferation and cell viability as measured with a commercial proliferation-apoptosis assay in which assay colour at 420 nm is directly proportional to cell density. One-way ANOVA was performed with Prism (version 7). Findings: Ishikawa cells were sensitive to AEA-mediated cytotoxicity in a pseudo dose-dependent manner. AEA caused a significant decrease in cell number only at concentrations above 1000 nM (mean 28·1% [SE 7·8], n=12; p<0·0001). The decrease in cell viability that occurred at 4, 18, and 24 h was partly restored at 48 and 72 h suggesting that the AEA growth inhibitory effect is time limiting. Interpretation: Our results show that AEA induces a decrease in Ishikawa cell number probably through inhibition of cell proliferation rather than cell death. These data suggest that the increased plasma and tissue AEA concentrations observed in patients with endometrial cancer is a counter mechanism against further cancer growth and points to the endocannabinoid system as a potentially new therapeutic target. Funding: University Hospitals of Leicester NHS Trust.